Preparation of Poly-(Methyl vinyl ether-co-maleic Anhydride) Nanoparticles by Solution-Enhanced Dispersion by Supercritical CO2 - Yong-Qiang Kang (Materials, 2012)
The supercritical CO2-based technologies have been widely used in the formation of drug and/or polymer particles for biomedical applications. In this study, nanoparticles of poly-(methyl vinyl ether-co-maleic anhydride) (PVM/MA) were successfully fabricated by a process of solution-enhanced dispersion by supercritical CO2 (SEDS). A 23 factorial experiment was designed to investigate and identify the significance of the processing parameters (concentration, flow and solvent/nonsolvent) for the surface morphology, particle size, and particle size distribution of the products. The effect of the concentration of PVM/MA was found to be dominant in the results regarding particle size. Decreasing the initial solution concentration of PVM/MA decreased the particle size significantly. After optimization, the resulting PVM/MA nanoparticles exhibited a good spherical shape, a smooth surface, and a narrow particle size distribution. Fourier transform infrared spectroscopy (FTIR) spectra demonstrated that the chemical composition of PVM/MA was not altered during the SEDS process and that the SEDS process was therefore a typical physical process. The absolute value of zeta potential of the obtained PVM/MA nanoparticles was larger than 40 mV, indicating the samples’ stability in aqueous suspension. Analysis of thermogravimetry-differential scanning calorimetry (TG-DSC) revealed that the effect of the SEDS process on the thermostability of PVM/MA was negligible. The results of gas chromatography (GC) analysis confirmed that the SEDS process could efficiently remove the organic residue.